Signaling pathways directing the movement and fusion of epithelial sheets: lessons from dorsal closure in Drosophila. - Harden, N. (Differentiation, 2002)
Wound healing in embryos and various developmental events in metazoans require the spreading and fusion of epithelial sheets. The complex signaling pathways regulating these processes are being pieced together through genetic, cell biological, and biochemical approaches. At present, dorsal closure of the Drosophila embryo is the best-characterized example of epithelial sheet movement. Dorsal closure involves migration of the lateral epidermal flanks to close a hole in the dorsal epidermis occupied by an epithelium called the amnioserosa. Detailed genetic studies have revealed a network of interacting signaling molecules regulating this process. At the center of this network is a Jun N-terminal kinase cascade acting at the leading edge of the migrating epidermis that triggers signaling by the TGF-beta superfamily member Decapentaplegic and which interacts with the Wingless pathway. These signaling modules regulate the cytoskeletal reorganization and cell shape change necessary to drive dorsal closure. Activation of this network requires signals from the amnioserosa and input from a variety of proteins at cell-cell junctions. The Rho family of small GTPases is also instrumental, both in activation of signaling and regulation of the cytoskeleton. Many of the proteins regulating dorsal closure have been implicated in epithelial movement in other organisms, and dorsal closure has emerged as an ideal model system for the study of the migration and fusion of epithelial sheets.